Dynamic contrast-enhanced MRI perfusion of normal muscle in adult hips: Variation of permeability and semi-quantitative parameters. Issue 108 (November 2018) - El Rafei, Mazen; Teixeira, Pedro; Norberciak, Laurène; Badr, Sammy; Cotten, Anne; Budzik, Jean-François
Abstract: The purpose of this prospective study was to ascertain the degree of variation of semi-quantitative and permeability parameters on DCE-MRI of normally appearing striated muscles. Dynamic contrast-enhanced MRI of the right hip was performed in 20 women and 24 men. Mean age was 39.1 ± 12.4 years. Two regions of interest (ROI) were drawn in twelve muscles of anterior, medial and gluteal compartments: a free-form ROI covering the largest muscle section and a smaller elliptical ROI. Semi-quantitative and permeability parameters were calculated using the extended Tofts model. Statistical analysis was performed with a linear mixed model to assess perfusion parameters variation. Intra- and inter-observer agreements were assessed. The intra-observer agreement was considered to be good for free-form ROI (minimum Intra-Class Coefficient (ICC) = 0.72) and moderate for elliptical ROI (minimum ICC = 0.51), while the inter-observer agreement was considered to be bad in both cases (minimum ICC = 0.11). There was a high inter-individual variation in most of the perfusion parameters evaluated. The average coefficients of variation were: Time To Peak = 9%, Area Under the Curve = 44%, Ve  = 61%, Kep  = 90%, Initial Slope = 99%, and K trans  = 128%. A considerable variation in resting muscle perfusion parameters was seen. This could lead to errors in the analysis of muscle DCE-MRI studies or oncologic/non oncologic studies using muscle as a referential. Further studies targeted on acquisition protocols and post-processing software are necessary to improve the performance of muscle MR perfusion.